Kualitas profesionalisme penyiar Radio Jakarta Islamic Centre 107.7 FM dalam program Bincang Bisnis Muslim (BBM) - Pratama, Amalia Rizki (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
Abstract The success of radio that has survived to this day cannot be separated from the role of radio broadcasters. A radio broadcaster is someone who guides the course of a radio program. Broadcasting is one of the most interesting professions to pursue. In this profession, broadcasters must be able to attract listeners’ attention only through sound, of course, there are many skills and expertise that need to be mastered in order to become a professional broadcaster and attract a lot of listeners’ interest. In carrying out their duties as radio broadcasters, of course, they must act professionally like in other professions. A radio broadcaster is required to always be communicative in bringing a broadcast program accompanied by sufficient knowledge, especially on things that are being discussed, this makes the broadcaster must always have the enthusiasm and motivation to continue learning and not easily give up. For this reason, a broadcaster needs a professional attitude. This study aims to determine how the broadcasters of Radio JIC 107.7 FM maintain their professionalism in guiding the BBM program. The research method used in this study is a descriptive qualitative method, which describes the results obtained based on data collected through in-depth interviews with broadcasters and program directors at Radio JIC. The results of the research that has been carried out show that JIC radio broadcasters have behaved quite professionally in guiding the BBM program. The radio management also continues to strive to maintain the professional quality of broadcasters by holding special selections. In the future, JIC Radio Broadcasters will continue to maintain their professionalism by improving their skills through more training for broadcasters so that broadcasters can be more focused and better at carrying out their duties. Abstrak Keberhasilan radio yang tetap bertahan hingga sekarang tidak terlepas dari peran penyiar radio. Penyiar radio merupakan seseorang yang memandu jalannya sebuah acara radio. Penyiar merupakan salah satu profesi yang menarik untuk dijalani. Dalam profesi ini penyiar harus mampu menarik perhatian pendengar hanya lewat suara, tentunya banyak sekali keterampilan dan keahlian yang perlu dikuasai agar menjadi seorang penyiar yang profesional dan menarik banyak minat pendengar. Dalam menjalani tugasnya sebagai penyiar radio tentunya harus berlaku secara profesional sebagaimana profesi lainnya. Seorang penyiar radio dituntut untuk selalu komunikatif dalam membawakan sebuah program siaran yang disertai dengan pengetahuan yang cukup terutama pada hal-hal yang sedang ramai diperbincangkan, hal tersebut membuat penyiar harus selalu memiliki semangat dan motivasi untuk terus belajar serta tidak mudah putus asa. Untuk itu seorang penyiar memerlukan sikap yang professional. Penelitian ini bertujuan untuk mengetahui bagaimana penyiar Radio JIC 107.7 FM dalam menjaga profesionalismenya dalam memandu program BBM. Metode penelitian yang digunakan pada penelitian ini ialah metode kualitatif deskriptif, yaitu memaparkan hasil yang didapatkan berdasarkan data yang berhasil dikumpulkan melalui wawancara mendalam dengan narasumber penyiar dan program director di Radio JIC. Hasil dari penelitian yang yang telah dilakukan menunjukkan bahwa Penyiar radio JIC sudah berlaku cukup profesional dalam memandu program BBM. Pihak pengelola radio juga terus berpaya menjaga kualitas profesionalisme penyiar dengan mengadakan seleksi khusus. Kedepannya Penyiar Radio JIC akan terus menjaga profesionalismenya dengan meningkatkan skill melalui pelatihan yang lebih banyak untuk para penyiarnya agar penyiar dapat lebih fokus serta lebih baik lagi dalam menjalankan tugasnya.